Pemetrexed-Platinum With or Without Bevacizumab for Chinese Chemo-Naive Advanced Lung Adenocarcinoma Patients: A Real-World Study - Li, Xin; Huang, Jie; Qiu, Yao; Zhang, Qianyun; Yang, Shaoyu; Wu, Kan; Wang, Jiaoli; Wang, Limin; Ye, Jian; Ma, Shenglin; Xia, Bing; Chen, Xueqin (Frontiers in Pharmacology, 2021)
Despite recent advances in the treatment of advanced non-small-cell lung cancer (NSCLC), bevacizumab plus platinum-based doublet chemotherapy remains a commonly used first-line regimen. This study was conducted to compare the efficacy and safety of pemetrexed-platinum with or without bevacizumab in Chinese chemo-naive advanced lung adenocarcinoma patients in a real-world setting. We retrospectively collected 100 patients who received pemetrexed-platinum with or without bevacizumab (PP, n=46; Bev+PP, n=54) until disease progression or unacceptable toxicity. Clinical characteristics of patients were balanced except for the proportion of stage Ⅳb+c (Bev+PP and PP: 67.4% vs 37.0%, p=0.0066). Bev+PP significantly improved objective response rate (ORR, 65% vs. 30%, p=0.0004) and progression-free survival (PFS, 7.4 vs 6.8 months, p=0.009) but not overall survival (OS, 17.5 vs 15.0 months, p=0.553) compared with PP. Treatment (p=0.001), gender (p=0.008), adrenal metastasis (p=0.001) and liver metastasis (p=0.013) were independent risk factors for PFS. Patients with adrenal metastasis tended to be at the highest risk not benefiting from bevacizumab addition (HR[95%CI]: 2.244[0.6495-7.753]). The safety profile was acceptable, and grade ≥ 3 toxicity occurred similarly. This study showed that pemetrexed-platinum plus bevacizumab was effective compared to chemotherapy alone in Chinese patients with advanced NSCLC.